2011
DOI: 10.1038/cddis.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of serotonergic innervation and 5-HT1A receptor in the human spinal cord

Abstract: Serotonergic innervation of the spinal cord in mammals has multiple roles in the control of motor, sensory and visceral functions. In rats, functional consequences of spinal cord injury at thoracic level can be improved by a substitutive transplantation of serotonin (5-HT) neurons or regeneration under the trophic influence of grafted stem cells. Translation to either pharmacological and/or cellular therapies in humans requires the mapping of the spinal cord 5-HT innervation and its receptors to determine thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Serotonin staining in naïve animals identified bilateral fiber bundles adjacent to the lateral horn of the gray matter which descended throughout the length of the spinal cord. This pattern of staining is similar to what has been demonstrated in the published literature [ 46 ]. Double-labeling of naïve mouse spinal cord sections showed these serotonergic fibers stained positive for the neuronal markers neurofilament and MAP2, although neurofilament does not predominantly label these fibers [ 47 ].…”
Section: Resultssupporting
confidence: 90%
“…Serotonin staining in naïve animals identified bilateral fiber bundles adjacent to the lateral horn of the gray matter which descended throughout the length of the spinal cord. This pattern of staining is similar to what has been demonstrated in the published literature [ 46 ]. Double-labeling of naïve mouse spinal cord sections showed these serotonergic fibers stained positive for the neuronal markers neurofilament and MAP2, although neurofilament does not predominantly label these fibers [ 47 ].…”
Section: Resultssupporting
confidence: 90%
“…235,236 Wheel running following an incomplete SCI stimulates serotoninergic fibers regrowth and improves locomotor recovery. 237 In the human spinal cord, serotoninergic processes have been identified within the ventral horn surrounding motoneurons, as well as in the intermediolateral region, 238 similar to what is reported for rodents and non-human primates. The lack of monoamines after SCI is clearly detrimental for locomotor performance and providing exogenous monoamines to improve recovery definitely has potential for success, at least in animal models.…”
Section: From Step-training Dependent Plasticity To Functional Recovesupporting
confidence: 67%
“…The 5-HT expressed by these intraspinal neurons was dependent upon the absence of 5-HT fibers as 5-HT from the descending input repressed expression of 5-HT from these intraspinal neurons. In the human spinal cord, Perrin et al ( 2011 ) have mapped 5-HT profiles in the thoracic and lumbar segments, finding a similar neuroanatomical localization to that of rodents and non-human primates where serotonergic processes were identified primarily within the ventral horn surrounding motoneurons as well as also in the intermediolateral region and in the superficial part of the dorsal horn.…”
Section: -Ht and Anatomical Localization Of Its Neural Pathwaysmentioning
confidence: 92%
“…The use of 5-HT receptor agonists in animals after an acute spinal transection has been shown to produce restoration of motoneuron excitability (Harvey et al, 2006 ; Li et al, 2007 ; Musienko et al, 2011 ; Sławińska et al, 2014a ). Work by various researchers have demonstrated that locomotor-activated spinal neurons, which constitute the CPG network, are innervated by serotonergic fibers (Johnson et al, 2002 ; Perrin et al, 2011 ; Sławińska et al, 2014b ) and that 5-HT is released within these sites during locomotor activity (Gerin et al, 2008 ). Together, these results have shown that serotonergic innervation and the availability of 5-HT in the lumbar cord (Antri et al, 2002 ) are critical for the restoration of hind limb motor function following SCI.…”
Section: Alterations In 5-ht Receptor Activity After Scimentioning
confidence: 99%